Enhancing Team Dynamics and Patient Outcomes: A Critical Analysis of Collaborative Practices Among Medical Clinic Workers - Saran , Waleed Saud bn; Alruwaili , Hazaa Lafi; Alanzi, Nashmia Murheq; Alenzi , Hadia Mutleq; Al Enizy, Jawaher Ali; Alanezi, Latifah Subhi; Alsaihati, Sajidah Mohammed; Alqahtani, Mohammed Mesfer Mohammed; Alarishy, Yahya Ali Yahya; alqahtani , Mansour Abdullah (Journal of Ecohumanism, 2024)
This article critically examines the impact of collaborative practices among medical clinic workers on team dynamics and patient outcomes. As healthcare delivery becomes increasingly complex, the importance of interdisciplinary teamwork among physicians, nurses, pharmacists, administrative staff, and support personnel has grown significantly. The study explores effective strategies such as team meetings, digital communication tools, and cross-training while identifying challenges like communication barriers, resource limitations, and hierarchical structures. Drawing on theoretical frameworks and empirical studies, the analysis highlights the positive correlation between robust teamwork and improved patient outcomes, including reduced medical errors and enhanced care quality. The findings emphasize the need for systemic changes, including training programs, leadership initiatives, and the integration of technology to optimize collaboration and patient care in medical clinics.